The Rigidity of Brazilian Public Expenditure in the Long Term (2018)
This paper studies the economic effects of the rigidity in the long term in the real public expenditure of Brazil. To determine this consequence it was applied the Computable General Equilibrium Model designed by Lofgren (2000) and calibrated from the Brazilian Social Accounting Matrix in 2013. The simulated equilibriums were presented for two likely scenarios in 2033 with respect to the validity or not of Constitutional Amendment No. 95. The calculation of probable situations differs with regard to education and health items. The findings complement existing impact studies and demonstrate a probable lower level of Gross Domestic Product, available national income, factorial labor income and slight consequences for the sectorial configuration and the trade balance.